Quality of athlete screening for high-risk cardiovascular conditions - A systematic review - Panhuyzen-Goedkoop, N. M.; Verbeek, A. L.; Goedkoop, R. J.; Malekzadeh, A.; Wilde, A. A.; Peters, R. J.; Jørstad, H. T. (Scandinavian Journal of Medicine & Science in Sports, 2023)
Background Sudden cardiac death (SCD) is the leading medical cause of death in athletes. To prevent SCD, screening for high-risk cardiovascular conditions (HRCC) is recommended. Screening strategies are based on a limited number of studies and expert consensus. However, evidence and efficacy of athlete HRCC screening is unclear.